TRANSLATING MULTICULTURALISM AT AN INDONESIAN PESANTREN - Umiarso El-Rumi (IAIN Tulungagung, 2019)
This paper discusses the concept and the practice of multicultural education at an Indonesian Islamic educational institution, the Pesantren Modern Walisongo. This paper employed a qualitative approach using a phenomenological type of research, and the technique of purposive and snowball samplings in gaining the data. Spradley model was applied to analyze the data; whereas the triangulation strategy and member check were implemented to gain data validity. This study concludes, the formation of the multicultural characters of santri uses the approach of integrating philosophical, spiritual, psycho philosophical, and socio religious-philosophical values.